The paradox of power : statebuilding in America, 1754-1920 - Campbell, Ballard C., 1940- (University Press of Kansas, 2021)
"The formation of the American state was something of a paradox, rising so quickly in power and wealth in the midst of an anti-statist political culture. While most people think the American state did not emerge until the twentieth century, The Paradox of Power challenges this notion, synthesizing a wealth of historical, political, legal, and economic scholarship to offer a reinterpretation of the development of the American state from the late colonial era through World War I. Ballard Campbell demonstrates that the American state developed consistently throughout the "long" nineteenth century (1754-1920). During these decades disconnected British colonies evolved into an affluent society with a greatly expanded capacity to govern, ranking the nation as a major world power by 1920. The Paradox of Power examines this complex evolution of the American state from two perspectives. The first describes the historical process of statebuilding, while the second links this historical narrative to five themes: geography, economic development, war and the military, individual identities including nationalism, and political capacity. Unlike most broad accounts of American governance, The Paradox of Power stresses the central role that state and local governments (including municipalities) played in America. The history of American governance has never been simply a story set in Washington"--